THE PHILOSOPHICAL BASIS OF THE PRINCIPLE OF PROPORTIONALITY - Marius ANDREESCU; Andra PURAN (Challenges of the Knowledge Society)
The proportionality is a general principle of law, signifying the ideas of balance, justice, responsibility and the needed adequate suiting of the measures adopted by the State to the situation in fact and to the purpose aimed by the law. The principle is expressly formulated in the European Union documents but also in the constitutions of other states. The normative or jurisprudential regulation of the principle explains the numerous preoccupations at scientific level to identify its dimensions. In this study, the principle of proportionality is analyzed from the perspective of the philosophy of the law, in order to try to identify its value dimensions that are to be found in the normative consecrations or in jurisprudence. The normative of jurisprudential dimension of proportionality, as a law principle has its content in the concepts and philosophical categories that make up the contents of the principle of proportionality, in the law philosophy’s main periods and currents. We consider that such a scientific attempt is useful, having into consideration the importance of this principle for the contemporary law. The principle of proportionality is an important guaranty in the observance of the human rights, mainly in situations in which their exercising is being restricted by the actions ordered by state’s authorities, being at the same time an important criterion to delimit the discretionary power from the power excess in the activity of state’s authority. In our opinion, only in the extent of our knowledge and understanding of the philosophical contents of this principle it is possible this one’s correct applying in jurisprudence. This study is aiming to be a pleading for the possibility and usefulness of law’s philosophy in this epoch dominated by juridical pragmatism and normativism.